Utility of Empirical Formulae for Computing Potential Evapotranspiration - Reddy, P R; Sekhar, A Chandra; Venkataramudu, J; Dayanand, T (Annals of Arid Zone, 2016)
Computing potential evapotranspiration (PEn, which is generally influenced by various weather parameters, is an important step in estimation of water requirements of crops. An attempt was made to utilise four prediction methods, recommended by FAO, for computing PET for Anantapur region. Modified Penman method was more suitable since a number of weather parameters are taken in to consideration. PET values from the other three methods can be converted into modified Penman values with the ratios worked Out.